Имена прилагательные, образованные от названий минералов - Даунене, З.; Судавичене, Л. (Kalbotyra, 1972)
The article deals with the lexical meanings and grammatical peculiarities of the adjectives belonging to this group. The material was collected from Soviet and Russian classical literature. The adjectives under analysis are notable for the abundance of shades of meaning. They are used as relative and qualitative adjectives; the latter being very frequent in fiction. The investigation of concrete meanings makes it possible to analise the semantics of adjectives, their functions and usage more profoundly.